Conflicts about class : debating inequality in late industrialism : a selection of readings - Lee, David J.; Turner, Bryan S. (London : Longman, 1996)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: sociale conflicten; sociale klassen; sociale ongelijkheid